Ali's pretty little lies : a Pretty little liars prequel novel - Shepard, Sara, 1977- (New York : HarperTeen, 2013)
A tale set in the seventh grade in the weeks leading up to Ali's murder reveals her plots against Emily, Hanna, Aria and Spencer, as well as a dark secret that has the potential to destroy everything.
Keywords: Secrecy -- Fiction; Popularity -- Fiction; Truthfulness and falsehood -- Fiction; Preteens -- Fiction